Discrimination of Artemisia afra from surrounding land cover types using field spectroradiometer data. (1st October 2016) - Dubula, Bambo; Tesfamichael, Solomon Gebremariam; Rampedi, Isaac Tebogo
ABSTRACT: This study investigated the utility of remote sensing to discriminate Artemisia afra from adjacent land cover types using continuum reflectance spectra acquired using a field spectrometer. Reflectance comparisons were made using original spectra as well as spectra simulated based on Landsat Enhanced Thematic Mapper Plus (ETM+) and Satellite Pour l'Observation de la Terre 5 (SPOT 5) bands at individual, plot and group levels. Results from all levels of analysis showed near-infrared (NIR) region to be consistent in discriminating A. afra from adjacent land cover types. The results of analysis using simulated Landsat ETM+ and SPOT 5 images showed the potential of extending the technique to actual remotely sensed data images, particularly using the NIR band. Further studies are encouraged to addressing some shortcomings of the study, such as sampling homogenous land cover types, creating ideal electromagnetic illumination scenarios and increasing sample size to improve the reliability of results for upscaling the technique to remotely sensed data.